Answer:
(2p(p - y - 1) + y^2)) / (y - p)^y.
Step-by-step explanation:
p^2 / (y - p)^y - 2p / (y - p)^y + 1 / (y - p)^y-2
The LCD is (y - p)^y
NOTE : (y - p)^y / (y - p)^y-2 = (y - p)^(y - (y - 2)) = (y - p)^2
So we have
(p^2 - 2p + 1( (y - p)^2) / (y - p)^y
= ( p^2 - 2p +y^2 - 2py + p^2) / (y - p)^2
= (2p^2 - 2py - 2p + y^2) / (y - p)^y
= (2p(p - y - 1) + y^2)) / (y - p)^y.
Answer:
Julie spent $5.46. Micah spent $27.30. Jeremy spent $33.99.
Step-by-step explanation:
Julie spent $5.46
Micah spent 5 times more than Julie, so multiply $5.46 by 5, which totals $27.30.
Jeremy spent $6.69 more than Micah, so add $6.69 to $27.30 to equal $33.99.
Answer:
5 ounces of milk
Step-by-step explanation:
Answer:
see below
Step-by-step explanation:
x = 63 and y = 27
180 - 117 Gives 63
The answer should be -192. I could explain in the comments if you would like. :)